GEOMETRY OF CRACKED SOLIDS AND PARAMETRIC RESONANCE - Sibiryakov B.P. (My University, 2002)
The paper addresses parametric resonances, the phenomena fraught with natural and technical risk which arise only in cracked solids and never in classical continuous media. The resonances are induced by periodic oscillations of media at an invariable phase and a wavelength equal to the mean size of their elementary blocks as soon as the oscillation amplitude is sufficient to overcome friction. It is suggested to theoretically investigate parametric resonances in cracked solids in terms of a model containing specific surface of cracks with length-inverse dimension, using new differential equations of motion and equilibrium of a higher order than the classical equations.